Receiving the home care service offered by certified care workers prior to a patients’ death and the probability of a home death: observational research using an instrumental variable method from Japan - Yasuki Kobayashi; Kazuhiro Abe; Atsushi Miyawaki; Haruko Noguchi; Hideto Takahashi; Nanako Tamiya (BMJ Open)
Objectives To assess the association between receiving the certified care workers’ home care service, which is provided by non-medical professionals prior to a patients’ death and the probability of a home death.Design Observational research using the full-time translated number of certified care workers providing home care service per member of the population aged 65 or above, during the year prior to patient’s death per municipality as an instrumental variable.Setting The certified care workers’ home care service covered by the public long-term care insurance (LTCI) system in Japan.Participants In total, 1 613 391 LTCI beneficiaries aged 65 or above who passed away, except by an external cause of death, between January 2010 and December 2013 were included in the analysis.Primary outcome measures Death at home or death at other places, including hospitals, nursing homes and clinics with beds.Results Out of all participants, 173 498 (10.8%) died at home. The number of patients who used the certified care workers’ home care service more than once per each month during 1, 2 or 3 months prior to the month of death numbered 213 848, 176 686 and 155 716, respectively. This was associated with an increased probability of death at home by 9.1% points (95% CI 2.9 to 15.3), 10.5% points (3.3 to 17.6) and 11.4% points (3.6 to 19.2), respectively.Conclusions The use of the certified care workers’ home care service prior to death was associated with the increased probability of a home death.